Extraocular muscle index as a novel indicator of inflammatory condition in graves’ ophthalmopathy patients - Wu, Fangkun; Huang, Jin; Wang, Mengdi; Qian, Zhenbin; Wang, Yaohua; Fang, Wei (Frontiers in Endocrinology, 2025)
PurposeThis study utilized the extraocular muscle index measured through computed tomography (CT) to objectively assess the condition of immune inflammation in patients with Graves’ ophthalmopathy.MethodsThis observational study included 50 control subjects and 50 patients diagnosed with graves’ ophthalmopathy (GO). The study collected mean platelet volume (MPV) alongside other serological indicators. Additionally, thyroid function parameters, clinical activity score (CAS), and NOSPECS score were documented. In the enrolled patients, the total extraocular muscle thickness was assessed using CT at the mid-orbital region posterior to the eyeball, with measurements obtained using Image-J software. The objective of this study was to investigate the inflammatory condition by analyzing the correlation between extraocular muscle thickness and blood indices, thereby providing a reliable predictor for clinical outcomes.ResultsIn patients with GO, the levels of neutrophil count (NC), lymphocyte count (LC), and platelet distribution width (PDW) were significantly elevated compared to the control group (p=0.024, p=0.016, and p=0.004, respectively). Conversely, the MPV exhibited a significant decrease (p=0.005). A linear regression analysis indicated a positive correlation between MPV and extraocular muscle thickness (r=1.356, p=0.014). Notably, MPV retained a positive correlation with extraocular muscle thickness even after adjusting for potential confounding factors such as age, CAS, NOSPEC, and thyroid function.ConclusionThe extraocular muscle index serves as a reliable predictor of the overall inflammatory status in patients with GO. Consequently, we can effectively assess the systemic inflammatory status of GO patients through orbital CT, thereby providing valuable references for clinical intervention.